The Positive Deviance of Feeding Practices and Carring With Nutritional Status of Toddler Among Poor Families (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
There are poor families with income less than minimum wage (IDR 1,900,000 / month) In Baru Village, Sarolangun Jambi. However, in reality the majority of toddler in the village have a relatively good nutritional status. The purpose of this study was to know the positive deviance of feeding practices and carring with nutritional status of toddler among poor families. This study used a cross-sectional study design. This research was conducted on April until August, 2016 in Village’s Baru, Sarolangun, Jambi. The sampling technique in this study was total sampling. The samples was 84 under five age children from poor families. Determination of nutritional status using indicators of Weight for Age, which refers to the standard Kemenkes RI. The data of positive deviance taken using a questionnaire tools. The data collected was analyzed by univariate and bivariat test(chi-square test). The results showed that the positive deviance of infant feeding practice habits (91,7%), toddler’s care (85,7%), nutritional status of toddler (90,5%) categorized was good. The conclusion, the are relationship between positive deviance of feeding practices and carring with nutritional status of toddler among poor families (p0,05).